Determinants of services exports and their impact on economic growth in selected Asian countries - Ahmad, Siti Asiah (2015)
In recent decades, services sector has been identified as a new engine for economic transformation in both developed and developing countries. Services trade, in particular, is regarded as a new source of income, especially for developing countries. Even though services trade only represent 20.2 per cent (2010) to total world trade, interestingly, recent trend shows that the share for developing countries in services trade increased to 32 per cent (2010) as compared with only 20 per cent in 1990. In addition, the share of services exports to total exports is increasing from 18 per cent to 30 per cent for the period of 1990 and 2010. Although, most of the developing countries are still net importers for services, there is a widespread belief among scholars and policy makers that there is great potential for services exports to grow further as new source of income for developing countries. The main purpose of this study is to empirically examine the determinants of services export and its impact on economic growth by using panel data in selected Asian countries. To achieve the first objective, static linear panel data model is applied through fixed and random effects model. Meanwhile, the second objective was tested by using panel dynamic OLS (DOLS) to capture the dynamic linkages among the selected variables. Annual data covering the period from 1985 to 2012 was utilized. The selected Asian countries are China,Hong Kong, South Korea, India, Iran, Indonesia, Malaysia, Philippines, Singapore, Thailand, Kuwait, Saudi Arabia and Turkey. The findings indicates that services exports in Asian developing countries are influenced by exchange rate, foreign income, foreign direct investment (FDI), value added of services, and communication facilities. As for second objective,it can be concluded that all of the macroeconomic variables tested are cointegrated in the long run. A services export also has a significant and positive impact on economic growth. The findings implies that the Asian developing countries have the opportunity to compete in exporting services globally provided that these countries could exploit their potential especially through stable exchange rate, promotion of services sector and other sector which are using services as intermediate input and also by enhancing the communication facilities. Moreover, since services exports found to a significant determinants of economic growth, Asian developing countries should focus more on developing appropriate policy measures to increase the productivity of the services sector.